2018
DOI: 10.3389/fphar.2018.00830
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effectiveness of Chinese Patent Medicine Tongxinluo Capsule for Secondary Prevention After Acute Myocardial Infarction: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Chinese patent medicine Tongxinluo capsule (TXL) is commonly used for cardio-cerebrovascular diseases. Previous research had demonstrated that TXL exhibited great clinical effects on the treatment of acute myocardial infarction (AMI), however there is a lack of systematic review. The purpose of this study was to evaluate the potential effectiveness and safety of TXL for secondary prevention in patients with AMI.Method: We searched 6 databases to identify relevant randomized controlled trials (RCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…An RCT involved adjunctive treatment improved vascular function and structure effectively, and was well tolerated, suggesting they may become a novel secondary prevention approach (48). Interestingly, in addition to Danshen and Gegen, RCTs (29,49) show that Qi-Shen-Yi-Qi Dripping Pill and Tongxinluo Capsule can also be used as a supplementary and alternative therapy for secondary prevention of MI. In general, TCM is notably effective and safe in the prevention, treatment, and health care of CAD compared with mimetic, placebo, or western medications (Table 1 and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…An RCT involved adjunctive treatment improved vascular function and structure effectively, and was well tolerated, suggesting they may become a novel secondary prevention approach (48). Interestingly, in addition to Danshen and Gegen, RCTs (29,49) show that Qi-Shen-Yi-Qi Dripping Pill and Tongxinluo Capsule can also be used as a supplementary and alternative therapy for secondary prevention of MI. In general, TCM is notably effective and safe in the prevention, treatment, and health care of CAD compared with mimetic, placebo, or western medications (Table 1 and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our research is not limited to MIRI treatment, and preadminis-tration also means that the candidate is potential to have a preventive effect for coronary heart disease. For example, such as the marketed compound Danshen tablets, compound Danshen dripping pills, and Tongxinluo capsules can prevent and treat coronary heart disease and be helpful for patients at risk of cardiovascular disease [43][44][45]. In fact, in the field of basic research, preadministration of the myocardial ischemia model is a common and recognized method [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…ere was benefit in the use of Tongxinluo (TXL) capsule for secondary prevention after acute myocardial infarction (AMI). A systematic review and meta-analysis of randomized controlled trials indicated that TXL improves cardiac function; regulates blood lipid total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-C (LDL-C); and decreases the level of hs-C-reactive protein (hs-CRP) [12]. A meta-analysis indicated that Huoxue Huayu therapy (HXHY) is an effective and safe therapy for patients after percutaneous coronary intervention (PCI).…”
Section: The Therapeutic Effect Of Tcm In Chdmentioning
confidence: 99%